1,5-Bis(2-oxoindolin-3-ylidene)thiocarbonohydrazide tetrahydrofuran monosolvate - Pezeshkpour, Shaghayegh; Khaledi, Hamid; Ali, Hapipah Mohd (International Union of Crystallography, 2012)
In the thiocarbonohydrazide molecule of the title compound, C17H12N6O2S·C4H8O, the terminal indolin-2-one ring systems make a dihedral angle of 20.13 (6)° with each other. Two intramolecular N—H⋯O hydrogen bonds are present, each of which generates an S(6) ring. In the crystal, N—H⋯O hydrogen bonds lead to a molecular chain running along the b axis. The tetrahydrofuran solvent molecule is disordered over two orientations in a 0.561 (11):0.439 (11) ratio.